Congenital Systemic Fungus Infection in Twin Prematurity—A Case Report and Literature Review - Chen, Wei-Yu; Chen, Shu-Jen; Tsai, Shu-Fan; Tsao, Pei-Chen; Tang, Ren-Bin; Soong, Wen-Jun (American Journal of Perinatology Reports, 2015)
Congenital candidemia sepsis is a serious condition especially for the prematurity. Early recognition is always not the scenario and this leads to high morbidity and mortality. Twin pregnancy complicates the problems further. This report presents a case of congenital candidiasis in a twin preterm and literatures review of five twin pairs with the same scenario. In conclusion, for twin prematurity, if one is suspected to have invasive candidiasis, both of them should receive a full course of antifungal therapy through the intravenous route.
Keywords: congenital candidemia; twin; prematurity; sepsis